Body Mass Index as a Parameter of Running Speed - indri seta septadina; Tri Suciati; Ha Sakinah Se (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Speed is determined by several factors such as anatomical and physiological factors. Body Mass Index (BMI) is one of an indicator from anthropometric measurement that is relevant to distinguish the capacity and performance of athletes. The aim of this study is to investigate the correlation between BMI and running speed. It was an observational research with cross-sectional design of 35 students of Athlete High School in Palembang. students. The primary data was taken from anthropometric measurements (stature meters, weight scales, meters) and assessment of 50 meters running speed tests. Data analysis was executed by using Pearson or Spearman correlation test in SPSS. The BMI of subjects varied from 17.05 to 27.12 with mean 21.48. The running speed of subjects varied from 5.67 to 8.17 m/s, with an average of 6.78 m/s. The bivariate analysis showed that there was a weak negative correlation between BMI and running speed (r = -0160). There was a weak negative correlation between BMI and running speed (r = -0160). A negative correlation means that the greater BMI then the less time it takes to run at a distance of 50 meters, in other words, the better performance of athletes.